The Problem of Composition and Independence of the Federal Supreme : Court in Iraq-An Analytical study of the First Amendment Law No. 25 of 2021 to the Federal Supreme Court Law No. 30 of 2005. - Abdulkarim Gazallani, Aso HamaShin (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
This study adequately addresses the problems facing the Iraqi Federal Supreme Court in terms of its formation mechanism under the Iraqi State Administration Law of 2004 and the Iraqi Constitution 2005 with the Federal Supreme Court Law No. 30 of 2005 and its first amendment Law No. 25 of 2021, as well as the extent of the Court’s independence from the Judicial authority. This is a result of textual contradictions between the constitution and the law of the court, on the one hand, this led to creating large gap between the components of the judiciary in Iraq, and on the other hand, this matter coincided with the court’s endeavor in some of its decisions to remain without reference in terms of legal, administrative and financial terms. Consequently, that led to the death of one of its judges and the other judge retiring for health reasons that led to the obvious paralysis and disruption of that service. This resulted in preventing this court from holding its sessions and proceeding continuing to issue judicial decisions and rulings the reason being inability to hold sessions with the unanimity of its members. This continued until the law of the court was first amended by Law No. 25 of 2021 by the Iraqi legislator who personally raised the problems of the court; and this resulted in a newly amended law to refer the former members of the court to retirement. The court judges are replaced with new members in the new amended law, who comprises nine original members and four reserve judges. With this matter, the amended law also fell into the quagmire of constitutional violations for limiting members to judges only, excluding legal scholars and Islamic jurisprudence experts, regardless of the fact that the amended law stipulated this fact in Article 92/Second of the 2005 Iraqi constitution. Additionally, the law was passed by a simple majority of members of the Iraqi Council of Representatives, knowing that the constitution specified a two-thirds majority as a legal quorum for voting, not a simple majority. This, of course, is a fundamental formal flaw in the law.